A study on consumers' experiences and avoidances of mobile shopping application advertisements - Keem, Jee Su; Lee, Seunghee (Journal of global fashion marketing, 2018)
This study aimed to analyze consumers' experiences and avoidances of mobile shopping application advertisements. Preceding mobile shopping studies were reviewed to meet this objective and to understand mobile shopping characteristics; consequently, mobile shopping application advertisement types were selected for analysis. This study sampled 200 male and female consumers in their 20s and 30s who had experience in using mobile shopping applications. Their experiences regarding shopping application advertisements, their clicks and irritations, and particularly their avoidance of these advertisements were analyzed by advertisement type. Finally, subjects' experiences in avoiding mobile shopping application advertisements were discussed. This study's results can be summarized as follows: First, the group with no experience in mobile shopping application advertisements demonstrated a higher tendency to avoid these advertisements. Second, the group with experiences in clicking on mobile shopping application advertisements tended to avoid them more than their counterpart group. Third, the "reward" ad type was most favored by consumers, and alternatively, the "pop-up" ad type was shown to irritate both genders. In summary, the companies that create these application advertisements are advised to operate their own mobile shopping application advertisements with caution, to prevent irritating consumers or forcing them to avoid their advertisements.